Review of the genus Antoniejanse Kemal & Koçak, 2005 (Lepidoptera, Gelechiidae, Litini), with description of four new species - Bidzilya, Oleksiy V.; Rajaei, Hossein (Zootaxa, 2024)
The southern African genus Antoniejanse Kemal & Koçak, 2005 is revised. Seven species are recognized here as valid, of which four species are described as new for science from South Africa (A. varii sp. nov. and A. tenebrosa sp. nov.) and Namibia (A. minima sp. nov. and A. mediopunctata sp. nov.). One new combination is proposed: Antoniejanse sagittata (Bidzilya, 2019) comb. nov. (ex Paratelphusa). All species of Antoniejanse are re-diagnosed. Wing patterns, as well as male and female genitalia are depicted. An identification key to all species of the genus is provided and the checklist of the genus is updated.